2012
DOI: 10.1258/ar.2012.110697
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of patients with persistent vascular obstruction on computed tomography pulmonary angiography 6 months after acute pulmonary embolism

Abstract: Persistent pulmonary vascular obstruction on 6-month CTPA did not predict long-term adverse outcome events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 8 publications
0
26
2
Order By: Relevance
“…Overall, 192 of 1294 patients with RPO had recurrent VTE (14.8%; 95% CI 13.0‐16.8), as compared with 176 of 2178 without RPO (8.1%; 95% CI 7.0‐9.3). The presence of RPO, either on CT angiography or on lung scan, was associated with an increased risk of recurrent VTE without significant heterogeneity (16 studies; 3472 patients; OR according to the random‐effects model, 2.22; 95% CI 1.61‐3.05; I 2 = 26%) (Figure ) . The association was confirmed after amending for zero cells (OR 2.13; 95% CI 1.56‐2.90) and after excluding from the analysis the study by Meneveau et al, in which RPO was assessed at an early stage (OR 2.11; 95% CI 1.52‐2.93).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Overall, 192 of 1294 patients with RPO had recurrent VTE (14.8%; 95% CI 13.0‐16.8), as compared with 176 of 2178 without RPO (8.1%; 95% CI 7.0‐9.3). The presence of RPO, either on CT angiography or on lung scan, was associated with an increased risk of recurrent VTE without significant heterogeneity (16 studies; 3472 patients; OR according to the random‐effects model, 2.22; 95% CI 1.61‐3.05; I 2 = 26%) (Figure ) . The association was confirmed after amending for zero cells (OR 2.13; 95% CI 1.56‐2.90) and after excluding from the analysis the study by Meneveau et al, in which RPO was assessed at an early stage (OR 2.11; 95% CI 1.52‐2.93).…”
Section: Resultsmentioning
confidence: 82%
“…The association between RPO and recurrent VTE was confirmed in studies assessing RPO on lung scan (11 studies; 2916 patients; OR 2.21; 95% CI 1.63‐3.01; I 2 = 16%), but not in studies assessing RPO on CT angiography, although there was significant heterogeneity (five studies; 556 patients; OR according to the random‐effects model, 2.56; 95% CI 0.82‐7.94; I 2 = 52%) …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…55 Whether residual pulmonary vascular obstruction after PE is a risk factor for recurrence remains unclear. 56 In a cohort of 157 patients, complete PE resolution had occurred in 84.1% of the patients 57 In a different study, Meneveau et al found an association between residual pulmonary vascular obstruction evaluated before hospital discharge and long-term adverse outcome (also recurrent PE). 12 Ongoing studies will probably clarify this issue (NCT01781858).…”
Section: Other Determinants Of Recurrencementioning
confidence: 97%
“…The study was underpowered to assess short-term outcomes because of a low rate of in-hospital adverse events. However, we followed the long-term evolution of the patients after hospital discharge, and we found that neither residual vascular obstruction on the 6-month computed tomography pulmonary angiography [3] nor persistent echocardiographic signs or right ventricular pressure overload 6 months after the PE [4] predicted long-term adverse outcome events.…”
mentioning
confidence: 99%